Adipose Tissue and Adipokines: The Association with and Application of Adipokines in Obesity. (17th September 2014) - Khan, Muhammad; Joseph, Frank
Abstract : 2014 marks the 20th anniversary of adipokines. Through the identification of leptin, our perceived understanding of adipose tissue was changed instantaneously. From a simple dormant site of energy storage, adipose tissue is now recognized as an integral hub of various hormones known as adipokines. Although great strides have been made in characterizing these hormones in health, research also shows they are significantly implicated in a series of pathologies. One such condition is obesity. Defined as an excess of adipose tissue, obesity remains one of the greatest healthcare epidemics of the 21st century. With no definitive treatment, attention has shifted to understanding the role of adipokines in obesity. This review provides an introduction to the salient obesity-related adipokines and their possible application as a treatment for obesity.